Cultural Shifts in Maranggap among the Batak Community: The Impact of Christianity and Modernization - Ambarita, Jenri; Simanihuruk, Sudirman; Siahaya, Agusthina; Elda, Elda (Analisa: Journal of Social Science and Religion, 2025)
The Maranggap tradition in Batak Toba society carries deep social and traditional medical values. This ethnographic qualitative research examines the changes and continuities of Maranggap in the face of Christian influences and modernization, as well as their impact on collective identity and social cohesion. The study was conducted over six months (January–June 2024) in Humbang Hasundutan, Sidikkalang, Girsang Sipangan Bolon, and Tanah Jawa. Data were collected through in-depth interviews with customary leaders, religious figures, and community members, as well as participatory observation. Thematic analysis was used to identify key patterns and themes. Findings reveal that in Girsang Sipangan Bolon and Tanah Jawa, Maranggap has been replaced by Christian-style thanksgiving rituals, while in Humbang Hasundutan and Sidikkalang, it is still practiced with modifications. Christian influences are reflected in the use of prayers, hymns, and new interpretations of traditional elements. Modernization has led to changes in food offerings, event organization through digital platforms, and a decline in the role of traditional birth attendants due to medical regulations. However, traditional health practices—such as marbara (smoke healing) and the use of betel leaves, turmeric, and ginger—remain relevant. The integration of traditional and modern medical knowledge is growing, and technology aids in preserving and disseminating Maranggap’s health-related wisdom. This study highlights how traditional values adapt within shifting religious and contemporary contexts, and the ongoing challenge of sustaining cultural identity in a transforming society.